(untitled) (Revista Apotheke, 2023)
This article is a report/record of the process of an improbable meeting with ancestry that emerged during ceramics workshops held in Cambé, Paraná, in the year 2021. The workshop actions triggered a series of reflections on my own ancestry. Therefore, seeking to respond to these concerns, I relied on two authors who think and reflect on memory, which are: Michael Pollak and Achille Mbembe. The first one contributes with its discussion about the concepts of “underground memories” and “inherited memory”. The second, in turn, opposes the idea of ​​underground and official memory, conceiving the idea that the power of memory is not in narrating a reliable story, but in its fabulation movement. Other theorists who contribute to the discussion are also mentioned, as well as artists who, in one way or another, address these questions in their works.